A synoptic review of MoS2: Synthesis to applications. (April 2019) - Krishnan, Unni; Kaur, Manjot; Singh, Kulwinder; Kumar, Manjeet; Kumar, Akshay
Abstract: Molybdenum disulphide is established as multi-functional and multi-utility material due to its capability to display varying properties as it transforms from bulk to nanoscale. It has strengthened its importance in conventional industry in its bulk form as efficient lubricant. Its conversion from indirect to direct band gap with change of size has led to its usage as semiconductors in electronics industry. Few prominent domains which have recently found its utility are in flexible electronics, transparent transistor devices, and other co-opted fields for biological and chemical applications etc. In this work, an attempt is made to compile and encapsulate all aspects related to material with a brief description of structure, synthesis, properties and applications, so as to provide useful information for researchers and engineers. Highlights: Provides an insight into various structures and allotropes of MoS2 . Discusses various types of synthesis process along with their merits and demerits. Various properties are discussed with proper references for understanding its unique features. Applications of MoS2 in various domains are illustrated.